Knowledge Management System Model Development for Higher Technical Vocational Education - Eduardus Dimas Arya Sadewa; Romadhani Ardi; Amalia Suzianti (Institut Teknologi Sepuluh Nopember, 2019)
Knowledge management extensively applied in enterprise because it significantly effect on enterprise effectiveness and innovation strategy. In order to create professionalism in form of competencies, education institution also implemented knowledge management concept. Education institution as a knowledge business is a suitable form for a knowledge management development, especially in vocational education. With practical approach methods and strong industrial relationship in order to improve their student skills, vocational education has plenty of knowledge sources to create knowledge as institutions intangible asset. From prior study, knowledge management system in vocational education is unstructured. This study focus in developed a KMS model in higher vocational education institution. The model showed that relation between organization environment and KM infrastructure effect on knowledge flow. KM assessment level and knowledge flow configured KM strategy to establish KM roadmap. The KMS model test on Polman Astra institution.